Concentrated solar energy used for heat treatment of Ti6Al4V alloy manufactured by selective laser melting. (October 2018) - Chicos, Lucia-Antoneta; Zaharia, Sebastian Marian; Lancea, Camil; Pop, Mihai Alin; Cañadas, Inmaculada; Rodríguez, Jose; Galindo, Jose
Highlights: Heat treatment of SLM Ti6Al4V alloy in solar furnaces was carried out. Concentrated Solar Energy (CSE) in heat treatment of SLM Ti6Al4V alloy was used. Heat treatments below and above β-transus of SLM Ti6Al4V alloy were performed using CSE. Microstructure and microhardness of heat treated SLM Ti6Al4V alloy were analyzed. Heat treatment using CSE and results are reported for the first time. Abstract: Ti6Al4V alloy manufactured by Selective Laser Melting (SLM) technology was heat treated for the first time in solar furnaces on Plataforma Solar de Almeria, Spain. This paper focuses on demonstrating feasibility of using Concentrated Solar Energy (CSE) to heat treatment of the Ti6Al4V alloy produced by SLM as a new approach of heat treatment and an alternative to conventional techniques. SLM process is characterized by a local high heating followed by fast solidification and rapid cooling, resulting in a microstructure consisting of a fine martensite called α′ phase. Long columnar original β grains, with the inside original α′ microstructure, were found in the as-fabricated SLM Ti6Al4V. Specimens were heat treated both in the horizontal (SF40) and vertical (SF5) furnace using CSE, below and above the β-transus, under argon atmosphere and a heating rate of 60 °C/min. Heat treatments below β-transus led to transformation the α′ initial microstructure into a mixture of α and β, but after some treatments the initial characteristics of the microstructure were maintained and the columnar prior β grains remained visible in the cross section of the specimens. Treatments above β-transus transformed the original α′ microstructure into a lamellar α + β one and they also led to formation of α colonies. Specimens have a slight weight gain after heat treatment due to contamination of SLM Ti6Al4V during heat treatment and alpha case formation. Specimens subjected to heat treatments at high temperatures close to β-transus (850 °C) and above β-transus (1015 °C and 1050 °C) have the highest variation in weight. After heat treatments, microhardness of the most specimens was slightly decreased comparing with the microhardness of as-fabricated specimens. Dispersion of microhardness values of the heat treated specimens is greater than the as-fabricated SLM Ti6Al4V.